VÝRAZY (a + b)2 = a2 + 2ab + b2 = (a+b).(a+b) a3 + b3 = (a + b). (a2 - ab + b2 ) (a - b)2 = a2 - 2ab + b2 = (a-b).(a-b) a2 - b2 = (a + b) . (a – b) (a + b)3 = a3 + 3a2b + 3ab2 + b3 a3 + b3 = ( a + b) . ( a2 - ab + b2 ) (a - b)3 = a3 - 3a2b + 3ab2 - b3 a3 - b3 = ( a - b) . ( a2 + ab + b2 ) MOCNINY S PRIRODZENÝM EXPONENTOM ra n + san = (r + s) . a n am . a n = a m+n an . bn = (a . b) n am : an = am-n (a . b .c) n = an . bn cn MOCNINY S CELÝM ČINITEĽOM a0 = 1  mocnina an mocniteľ základ mocniny ODMOCNINY